Factores que inciden en el sindrome de ovario poliquistico en mujeres en edad fertil - Ajila Del Rosario, Segundo Eduardo (2018)
This research was conducted through the analysis of a real case of a patient admitted to the Teofilo Davila Hospital in the city of Machala. The main objective of this case analysis was to determine factors affecting in polycystic ovary syndrome, to improve the quality of life of women in fertile age, which used the analysis of scientific articles. Each one of the authors tells us in their published articles about the different way that develops the polycystic ovary syndrome, this being a public health problem that affects women aged 90%, many women are unable to conceive during long time, only 26% can become pregnant, patients with this syndrome do not come to know this type of problem, even detected in the final stage of pregnancy, being the case that was investigated, this problem causes complications that put often at risk the welfare of the mother as of the fetus, for that the analysis of each of these items allowed us to assess the risk factors that are present for this pathology, using to develop the above look for alternatives of solution that allows a greater prevention in this type of patients and reduce its complications. The first chapter describes a little about the generality of the object of study in which is mentioned the characteristics and symptoms with which income patient, in chapter II tells us about the origin of the disease and its evolution, also described which indicates each of the authors through their research, in chapter III are the methodological process which was used for the elaboration of the present research showing the type of research, the type of study, methods and the techniques used. Chapter IV talks about all the description and argumentation of the results obtained in the case study of the patient enters the House of health, also the conclusions responds to the main objective of the research and were developed the respective recommendations according to the objectives and design of the process of nursing care with the planning of care that will allow the improvement of the health of patients with such problems and thus contributing to the value of the research. Polycystic ovary syndrome may develop through economic, environmental and genetic factors, and has a direct connection with obesity, so that mention is made of the main factors in this clinical case study research of risk that will affect the development a polycystic ovary, our best tool we can use is the development of a process of nursing care for patients with this disease, helping to improve the quality of life and above all is You can prevent this syndrome with simple methods to prevent further complications.